Panel Discussion: Profiles in Surgical Innovation & Entrepreneurship - R. Carter Clement, MD, MBA; Kevin G. Shea, MD (Elsevier, 2024)
ABSTRACT: Innovation is crucial to the field of pediatric orthopaedic surgery. However, the process of developing a new surgical technology is complex and can be daunting. In this panel discussion, 5 surgeons who have successfully developed new technologies share their personal stories as well as mistakes made, lessons learned, and reflections on key questions related to innovation and entrepreneurship in the modern healthcare landscape. Key concepts: (1) There are many paths to successful innovation and entrepreneurship. (2) Building a capable team is key to success, especially for a practicing surgeon. (3) Fundraising typically benefits the entrepreneur by growing the overall pie. (4) Pediatric specialties are generally underserved by the medical device industry. (5) The Food and Drug Administration has taken steps to address this discrepancy.